Plastic surgery in gynaecology: Factors affecting women's decision to undergo labiaplasty. Mind the risk of body dysmorphic disorder: A review. (3rd May 2020) - Müllerová, Jana; Weiss, Petr
ABSTRACT: Aesthetic surgery of the female genitalia is on the rise. Many procedures are performed. Body dysmorphic disorder (BDD) is a psychiatric disorder and often goes unrecognized in plastic surgery. This review examines actual knowledge of plastic surgery in gynecology, knowledge of motivational factors of women, and BDD. We carried out a systematic electronic search. We used a combination of relevant keywords to construct the search strategy. Included studies were systematic reviews or primary studies published 1990–2017 and containing information about BDD. Reviewers independently assessed study eligibility, extracted data, and assessed quality, undertaking narrative synthesis. The research revealed a variety of plastic procedures available and why women consider undergoing labia reduction surgery.